Erythema Nodosum due to Pasteurella pseudotuberculosis. Issue 5651 (26th April 1969) - Wilkinson, D. S.; Turner, T. W.; Mair, N. S.
Abstract : Two children developed erythema nodosum due to Pasteurella pseudotuberculosis. Neither case showed typical signs of P. pseudotuberculosis infection, but this cause was shown by positive agglutination tests. It is suggested that this organism is a more common cause of erythema nodosum than is at present recognized.